A Saga-In-Progress: Challenges and Milestones on Our Way Toward the Nordic Core Values and Principles of Family Medicine/General Practice - Sigurdsson, Johann A.; Beich, Anders; Stavdal, Anna (Frontiers in Medicine, 2021)
Late in 2020, the Nordic Colleges of General Practice published a joint statement specifying what General Practitioners stand for and intend to act upon, our Core Values and Principles. In this article, the authors describe and analyze challenges and milestones encountered on our 50-year journey toward the creation of that document. The shaping of Family Medicine/General Practice as an academic discipline began in the 1960’s. During an initial, descriptive phase, the new specialty was defined, its educational curricula formulated, and the core competencies required to earn the title, Specialist in Family Medicine, were identified. Focus was not yet placed directly on the relationship between viable working principles and values, however. Then, the 1978 WHO Alma Ata Declaration affirmed health to be a fundamental human right, with primary health care as the heart of sustainable health care systems, indirectly mandating that the field of Family Medicine deliver value-based health care. A major step in that process was taken in 2001: The Norwegian College of General Practice launched their statement identifying the seven theses, Sju teser, that characterize the principles, purposes – and core values – of General Practice. Later, the Nordic colleges worked together to formulate the 2020 joint statement. We are confident that Family Medicine will continue to provide sustainable, relationship-based care, and to protect the human side of medicine. Sharing core values and principles can help us mobilize as effective advocates for our discipline and for our patients, the citizens whom we serve.